Comparison of Soft Tissue Parameters Around Dental Implants and Tooth-Supported Fixed Partial Dentures: A 6-Month Split Mouth Study - Jaswitha, V; Meghana, Gangolu; Ramanarayana, Boyapati; Reddy, K Tilak Vardhan; Kolaparthy, Lakshmikanth; Bhochhibhoya, Amar (Journal of Nepalese Prosthodontic Society, 2026)
Introduction: Prosthetic rehabilitation largely depends on the condition of the surrounding soft tissues. Difference in the biological attachment mechanisms may influence soft tissue responses in implant-supported restorations and tooth-supported fixed partial dentures (FPDs). This study aims to compare peri-soft tissue parameters around implant-supported restorations and tooth-supported FPDs using clinical and cone-beam computed tomography (CBCT) assessments.Methods: This prospective 6-month split-mouth clinical trial included 30 systemically healthy patients who required both a single dental implant (Group A) and a tooth-supported FPD (Group B).Plaque index, bleeding index, gingival recession, width of keratinised tissue, and esthetic score were recorded at baseline, 3 months, and 6 months following prosthetic loading. Gingival thickness and gingivalbiotype were evaluated using CBCT. Comparisons were performed using repeated measures ANOVA, unpaired t-tests and chi-square tests, with p ≤ 0.05.Results: Both groups showed a reduction in plaque index, although intragroup differences were not statistically significant. A significant intragroup change in bleeding index was observed in Group A. Gingival recession at 6 months was significantly lower in Group A compared to Group B (p = 0.007). No significant differences were found in keratinised tissue width or esthetic scores. Intergroup differences thickness was significant at 3 months at 2 mm level and at 6 months at 4 mm level. Gingival biotype remained stable.Conclusion: Both implant-supported and tooth-supported restorations exhibited satisfactory peri-soft tissue health when appropriate surgical, prosthetic, and maintenance protocols were followed. Implantsupported sites showed greater stability of marginal soft tissues and distinct soft tissue remodelling.